A study on the effect of a comparator device on shade selection among dental proper students in the University of the Philippines, Manila - Yupangco, Bernadette A.; Salvacion, Maria Lourdes (Adviser).
Despite the many technological advances in restorative dental materials, the "Color Problem" still remains to be a major problem to date. The success of the currently available aesthetic restorative dental materials depends largely on proper shade matching. This study aimed to determine whether the use of a color comparator device would aid in selection of shade for porcelain pontics. Three color comparator devices, colored gray, light blue and yellow were used in the selection of an unknown shade of a porcelain pontic by 52 dental proper students with normal color vision from the UP College of Dentistry. Results show that the use of a gray comparator device gives the most accurate selection of shade compared to the control (which did not use a comparator device), light blue comparator device ?and yellow comparator device. Statistical analysis showed that the use of the gray comparator device resulted in the highest percentage of correct answers. This set-up also has the least standard deviation and the smallest mean of the deviation of the guesses from the correct answers by the subjects. This was further confirmed using the Friedman Two-Way ANOVA Test.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.